Shadows over the European elections: Three scenarios for EU-sceptical parties after the 2019 elections - Nicolai von Ondarza; Felix Schenuit (Stiftung Wissenschaft und Politik (SWP), 2018)
For a long time, the elections to the European Parliament (EP) were considered second-order elections with little political significance. But for the elections coming in 2019, they are turning into a decisive vote on the future of the European Union (EU) - not only because the EP has gained in importance, but especially because the European party system is undergoing fundamental change. Whereas established parties are losing support, right-wing populist and EU-sceptical parties have been growing across Europe. At the same time, there are increased efforts to unite the traditionally fragmented EU-sceptical forces into a collective movement. Even though there is no drastic increase expected in the number of EU-sceptical Members of European Parliament (MEPs) in the next parliamentary term, a reorganisation of the EU-sceptical spectrum could be the prelude to drastic changes in the political structure of the EU.
Keywords: 320